Contribution of Body Mass Index to the Physical Fitness Level of Students - Boby Helmi; Rinaldi Aditya; Alan Alfiansyah Putra Karo Karo; Andi Nur Abady; Syahruddin; Heny Setyawati (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
The purpose of this study was to determine the contribution of body mass index to the level of physical fitness of junior high school students in Medan City in 2023. This study used descriptive analytic method. The sample amounted to 23 people, obtained by purposive sample. To determine the correlation of body mass index to the level of physical fitness is sought using the product moment formula. This research uses body mass index test instruments and physical fitness tests carried out to find out data on research variables, namely body mass index data and student physical fitness tests. From the results of statistical analysis, the correlation coefficient between body mass index and physical fitness is rcount = 0.55. To find out how much the contribution of body mass index to the level of physical fitness is calculated with R = (0.55)2 x 100% = 30.25%. The contribution is 30.25%. Thus the hypothesis that states there is a contribution of body mass index to the level of physical fitness of junior high school students in Medan City in 2023 can be accepted in this study. This research opens insights into knowledge for teachers, especially physical education teachers so that this information can be applied in schools.